The home as a work area in a pandemic and unintentional injuries - Sevilla, Elizabeth; Pérez-García, Luis (Horizonte Sanitario, 2024)
Objective: To know the characteristics of unintentional injuries in children at home during the pandemic and the opinion of parents about their belief about whether or not quarantine favors unintentional injuries in children.Material and methods: Descriptive study. Anonymous online survey method during home confinement. Those who work in schools were invited to participate to discuss it freely with parents and among their acquaintances. With the Excel program, the responses were analyzed through frequencies and percentages.Results: 75 forms were received. The average age of the children was 7 years. 32% of the households presented unintentional injuries. Falls and burns were the most frequent unintentional injuries. 72% do not believe that working from home and caring for children favors the frequency of unintentional injuries.And the exposure to the different dangers of the home, both in time and areas, increased due to not being able to go out. The fun was found in the areas of the home that were transformed into places of recreation.Conclusions: Safety should not be neglected at home by being in several activities during the pandemic. Child care is vital for prevent injuries. Keywords: Wounds and injuries; Child; Pandemics; Public housing; Work.